Folsom technology and lifeways
1 online resource
Keywords: This volume is an extensive collection of chapters discussing Folsom artifacts and sites, as well as innovative experiments undertaken to understand Folsom technology and lifeways. Public and private collections of Folsom artifacts were brought together with professional and amateur lithic analysts and knappers in an attempt to determine how the ancient stone tools were made and used. In addition, Folsom Technology and Lifeways summarizes interaction among knappers and analysts, and the attempts to replicate specific artifact types represented. It is a unique volume in that it examines the variation present in technology and behavior across a wide range of Folsom localities.